Carbocatalysed Oxidative C sp 2C sp 2 Homocouplings of Benzo‐Fused Heterocycles. Issue 16 (18th November 2015) - Wirtanen, Tom; Mäkelä, Mikko K.; Sarfraz, Jawad; Ihalainen, Petri; Hietala, Sami; Melchionna, Michele; Helaja, Juho
Abstract: Appropriate and fine‐tuned treatments of amorphous carbon (AC) involving aqua regia or concentrated HNO3 lead to oxidised carbon materials (oAC) which are able to catalyse 2, 2′‐ and 3, 3′‐homocouplings of various functionalised indoles with outstanding activity. This newly developed carbocatalysed C_sp^2 C_sp^2 bond formation can be achieved under mild thermal conditions. The study on the scope of the reaction revealed that the reaction can be extended to the homocoupling of other substrates of high synthetic interest such as 2‐naphthol, 2‐functionalised benzofurans and benzothiofurans. The characterisation of oAC with XPS together with ad hoc experiments aimed at blocking the active site revealed that the presence and distribution of CO functionalities is critical and correlates well with the catalytic activity. Such experiments provide solid support for elucidation of the mechanism, suggesting a quinone nature of the active CO groups, which are spontaneously regenerated by oxygen. This is confirmed by the fact that 2, 3‐dichloro‐5, 6‐dicyano‐1, 4‐benzoquinone (DDQ) is able to promote the coupling in a stoichiometric fashion. Abstract :